1994
DOI: 10.1203/00006450-199401000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Site of Action of Hypoxia in the Neonatal Pig Lung

Abstract: ABSTRAm. To determine the vascular site(s) of action of hypoxia in the neonatal pig, isolated lungs were perfused at a constant flow rate and left atrial pressure; arterial, venous, and double occlusions were performed. The distribution of the total pulmonary vascular resistance and the total dynamic vascular compliance were calculated using a model of the pulmonary circulation consisting of upstream, central, and downstream compliances and resistances upstream and downstream of central compliance. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…This is consistent with our previous studies in isolated perfused neonatal pig lungs (18,37). Furthermore, in isolated perfused lamb lungs, NOS inhibition increased basal perfusion pressure (21).…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with our previous studies in isolated perfused neonatal pig lungs (18,37). Furthermore, in isolated perfused lamb lungs, NOS inhibition increased basal perfusion pressure (21).…”
Section: Discussionsupporting
confidence: 82%
“…In isolated ferret lungs perfused at different flows and constant P LA , hypoxia increased P PA -P do markedly and P do -P LA slightly, and did not alter vascular compliance, indicating that HPV occurred mainly in the arterial region (225). Similar results were obtained in lungs of neonatal pigs (1369). These results are not necessarily inconsistent with inflow/outflow occlusion data discussed above, which suggested that HPV occurred predominantly in the middle compliant region (637,712,714,1648,1914).…”
Section: Iii) Vascular Volumesupporting
confidence: 89%
“…In fact, similar to our results, hypoxia is known to increase both the precapillary and postcapillary resistances in the lungs of newborn pigs. 21 On the other hand, it has been proposed that the developing pulmonary hypertension is caused by vascular structural changes from prenatal chronic stress rather than by the aspirated meconium.…”
Section: Discussionmentioning
confidence: 99%